Structural and content characteristics of innovative pedagogical system - Sergey L. Rykov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyzes theoretical approaches to the concept, structure and content of an innovative pedagogical system as a means of implementing new pedagogical ideas and mechanisms for forming creative thinking of teachers and students in various forms of the educational process. The purpose of the research is to identify the structural and content elements of the innovative pedagogical system. In the course of the research, the features and structure of the innovative pedagogical system are revealed, and the typology of teachers on the basis of their attitude to pedagogical innovations is presented. The author of the research defines the main components of the structure of innovative activity of a teacher, the system-forming elements of the pedagogical system, and the list of innovative pedagogical technologies. The analysis of scientific literature and personal pedagogical experience allowed us to establish a historical and pedagogical connection between the factors and conditions of the emergence of an innovative pedagogical system and the direction of its forms, methods and means. This relationship is established on the principles of goal setting, content compliance with goals. The practical significance of the research lies in the possibility of applying the identified structural and content elements of the innovative pedagogical system in pedagogical practice.